«Twelve Etudes» for guitar by Heitor Villa-Lobos: genre and style dimensions - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the article is to consider the cycle "Twelve etudes" for solo guitar by Heitor Villa-Lobos from the standpoint of the interaction of authentic Brazilian and academic European (baroque, romantic, modernist) genre-style models of creativity. World recognition and constant stage demand of the cycle is provided by a complex of essential advantages — the modern vocabulary of the composer, enriched with rhythm and intonation authentic elements of Brazilian culture, combined with virtuosity, the presence of the latest original techniques, high artistic qualities of the music and its genre and style diversity. Main objective of the study is to reveal in the cycle "Twelve Etudes" for solo guitar by Heitor Villa-Lobos metrorhythmic and intonation-melodic elements of Brazilian genres combined with linguistic innovations and stylistic interactions with academic European traditions. The novelty of the article consists in the introduction into the Ukrainian musicological circulation of the genre-style analysis of the cycle "Twelve Etudes" by H. Villa-Lobos, taking into account the specific direction of modern searches for musical vocabulary, which covers the renewal of the ideomatic resources of the instrument through performance techniques The methodology is based on an interdisciplinary approach and methods of historical, cultural, musicological, systemic, structural and functional analysis, applied to the study of the genesis of the choro, capoeira, tango, samba rhythmic archetype, primary ethnic sources, intonation-melodic manifestations, stylistic interactions and specific guitar technics in the composer's music. Results and conclusions. Historiographic information is taken into account, as well as certain events from the artist's creative biography, which highlight his inclination to guitar music in folk and academic directions. The influence of numerous ethno-expeditions of H. VillaLobos to different states of Brazil to get acquainted with the peculiarities of the music of different nationalities, their instruments, playing skills and orpheonic singing is determined. The role of ritual practices, carnival customs, martial arts music, timbre and rhythm-intonation richness of the national culture is characterized. The specifics of the author's search for a new vocabulary, which was based on the idiomatic resources of the guitar, were revealed. An analysis of the invented connections between the morphology of the modernist composer's thinking and the means of playing the instrument created by the author is offered. The peculiarities of operating with the techniques of fixing and sliding the same positions on the neck using open strings are revealed. The consequences of this technique, which lead to the formation of octatonic pitch phenomena inherent in the music of many European composers of the modernism era, are determined. Stylistic intersections of sound creation were traced: attention to phonic, coloristic, timbre qualities of sound; rhythmic innovations as factors of imitation of archaic layers and tribal ritual traditions of ancient local cultures; return to the vocabulary of masters of the past; articulation of folklore sources and their stylized models. Genre elements of choro, tango, samba, capoeira, Amazonian melodies and throat singing of the indigenous population of the country, Spanish Andalusian rhythm formation were studied. Imitations of the folk instruments Kavaquinho, Caipiro, Berimbau, Amazonian flutes, as well as the voices of the surrounding world as elements of the Brazilian soundscape are traced.